2021
DOI: 10.32996/jeltal.2021.3.1.2
|View full text |Cite
|
Sign up to set email alerts
|

The Acceptance of E-Learning Among ESL Primary School Students During Covid-19

Abstract: The past years have seen a strong focus in Malaysia on the increase of infusion of Information Communication Technology (ICT) in educational institutions to stimulate innovations and strengthen global economic competitiveness. The integration of ICT has transformed the Malaysian education system by reshaping the landscape of education, from teacher-centred to learner-centred education. However, the COVID-19 crisis has changed the landscape of the education system drastically. The educators have turned their fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 31 publications
2
6
0
Order By: Relevance
“…The education system needs to strengthen its mental health and psychosocial support to wider stakeholders beyond students either through in-person or virtual counselling. In terms of teaching and learning, while a few studies highlighted that virtual learning offers flexible, interactive, and effective lesson delivery [ 82 ], more studies have revealed that a physical class at school is the most effective delivery modality during the pandemic [ 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…The education system needs to strengthen its mental health and psychosocial support to wider stakeholders beyond students either through in-person or virtual counselling. In terms of teaching and learning, while a few studies highlighted that virtual learning offers flexible, interactive, and effective lesson delivery [ 82 ], more studies have revealed that a physical class at school is the most effective delivery modality during the pandemic [ 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…Positive effects of online learning system characteristics on both attitudes and BIs of EFL learners were also depicted in studies by Kanwal and Rehman (2017) and Pituch and Lee (2006). Like online learning system characteristics, the positive effects of PU of online learning on attitudes and BIs of EFL learners were also supported by most of the studies (Almarabeh, 2014;Farahat, 2012;Haleman & Yamat, 2021;Jiang et al, 2021;Natasia et al, 2022;Salloum et al, 2019;).…”
Section: Discussionmentioning
confidence: 67%
“…As stated in the literature, several research articles have shown that PU had a positive impact on the learners' BIs using online learning systems (Almarabeh, 2014;Farahat, 2012;Haleman & Yamat, 2021;Jiang et al, 2021;Natasia et al, 2022;Salloum et al, 2019). Some researchers indicated that the students with positive attitudes toward online learning systems had greater BIs toward them (Almarabeh, 2014;Farahat, 2012;Haleman & Yamat, 2021;Natasia et al, 2022). On the contrary, others claimed that learners' attitudes toward online learning systems had an insignificant effect on the learners' BIs toward them because the online learning systems were the only choice they had during the lockdown in the era of covid-19 (Jiang et al, 2021;Teo, Wong, & Chai, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Persistent disasters have led to more research to understand their evolving effects on local and global communities (IMF, 2020; UNDP, 2010b). Since the outbreak of coronavirus in 2019, many studies have aimed at understanding the consequences of the COVID-19 pandemic on different groups of students, primary school to college (e.g., Bentenuto et al, 2021;Chatterjee & Roy, 2020;Haleman & Yamat, 2021;Jain, 2020). Other research has investigated the schooling of learners with disabilities from different perspectives (Kiru, 2019;Nyeris & Koross, 2015), and most recently, on the impact of COVID-19 on learners with disabilities (Angode & Ressa, 2021;Ressa, 2020Ressa, , 2021, which points to the importance of education in disaster management and recovery process (Hoffmann & Muttarak, 2017;UNDP, 2010a).…”
Section: Literature Reviewmentioning
confidence: 99%